New Insights Into Acidithiobacillus thiooxidans Sulfur Metabolism Through Coupled Gene Expression, Solution Chemistry, Microscopy, and Spectroscopy Analyses - Camacho, David; Frazao, Rodolfo; Fouillen, Aurélien; Nanci, Antonio; Lang, B. Franz; Apte, Simon C.; Baron, Christian; Warren, Lesley A. (Frontiers in Microbiology, 2020)
Here, we experimentally expand understanding of the reactions and enzymes involved in A. thiooxidans ATCC 19377 S0 and S2O32- metabolism by developing models that integrate gene expression analyzed by RNA-Seq, solution sulfur speciation, electron microscopy and spectroscopy. The A. thiooxidans S2O32- metabolism model involves the conversion of S2O32- to SO42-, S0 and S4O62-, mediated by the sulfur oxidase complex (Sox), tetrathionate hydrolase (TetH), sulfide quinone reductase (Sqr) and heterodisulfate reductase (Hdr) proteins. These same proteins, with the addition of rhodanese (Rhd), were identified to convert S0 to SO32-, S2O32- and polythionates in the A. thiooxidans S0 metabolism model. Our combined results shed light onto the important role specifically of TetH in S2O32- metabolism. Also, we show that activity of Hdr proteins rather than Sdo are likely associated with S0 oxidation. Finally, our data suggest that formation of intracellular S2O32- is a critical step in S0 metabolism, and that recycling of internally generated SO32- occurs, through comproportionating reactions that result in S2O32-. Electron microscopy and spectroscopy confirmed intracellular production and storage of S0 during growth on both S0 and S2O32- substrates.